Physical-chemical and microbiological analysis of water reservoirs for industrial supply (Research, Society and Development, 2020)
The present work aimed to analyze the water quality of different reservoirs used to supply a small food industry located in the city of Campina Grande-PB, through the physical-chemical and microbiological parameters. The samples were collected in five different reservoirs and the following parameters were analyzed: pH, total dissolved solids, chlorides, residual chlorine, turbidity, total hardness. Microbiological analyzes were determined using the Colilert method. No high pH value was found, which would negatively affect the disinfection process, as it would accelerate the dissociation of hypochlorous acid. No residual chlorine concentration greater than 2.0 mg / L was observed in any sample. Therefore, the registered physical-chemical and microbiological analyzes are within the terms of Ordinance No. 2914/11. We recommend carrying out periodic control and monitoring of water quality, preventing the transmission of diseases.